Assessment of Right Ventricular Mechanics by 3D Transesophageal Echocardiography in the Early Phase of Acute Respiratory Distress Syndrome - Evrard, Bruno; Lakatos, Bálint Károly; Goudelin, Marine; Tősér, Zoltán; Merkely, Béla; Vignon, Philippe; Kovács, Attila (Frontiers in Cardiovascular Medicine, 2022)
Aims: To compare global and axial right ventricular ejection fraction in ventilated patients for moderate-to-severe acute respiratory distress syndrome (ARDS) secondary to early SARS-CoV-2 pneumonia or to other causes, and in ventilated patients without ARDS used as reference. Methods: Retrospective single-center cross-sectional study including 64 ventilated patients: 21 with ARDS related to SARS-CoV-2 (group 1), 22 with ARDS unrelated to SARS-CoV-2 (group 2), and 21 without ARDS (control group). Real-time three-dimensional transesophageal echocardiography was performed for hemodynamic assessment within 24 hours after admission. Contraction pattern of the right ventricle was decomposed along the three anatomically relevant axes. Relative contribution of each spatial axis was evaluated by calculating ejection fraction along each axis divided by the global right ventricular ejection fraction. Results: Global right ventricular ejection fraction was significantly lower in group 2 than in both group 1 and controls (median: 43% [25th-75th percentiles: 40-57] vs. 58% [55-62] and 65% [56-68], respectively: p<0.001). Longitudinal shortening had a similar relative contribution to global right ventricular ejection fraction in all groups (group 1: 32% [28-39], group 2: 29% [24-40], control group: 31% [28-38], p=0.6). Radial shortening was lower in group 2 when compared to both group 1 and controls (45% [40-53] vs. 57% [51-62] and 56% [50-60] respectively: p=0.005). The relative contribution of right ventricular shortening along the anteroposterior axis was not statistically different between groups (group 1: 51% [41-55], group 2: 56% [46-63], control group; 56% [50-64], p=0.076). Conclusions: During early hemodynamic assessment, the right ventricular systolic function appears more impaired in ARDS unrelated to SARS-CoV-2 when compared to early stage SARS-CoV-2 ARDS. Radial shortening appears more involved than longitudinal and anteroposterior shortening in patients with ARDS unrelated to SARS-CoV-2 and decreased right ventricular ejection fraction.